Genetic Virulence Profile of Enteroaggregative Escherichia coli Strains Isolated from Danish Children with Either Acute or Persistent Diarrhea - Hebbelstrup Jensen, Betina; Poulsen, Anja; Hebbelstrup Rye Rasmussen, Stig; Struve, Carsten; Engberg, Jørgen H.; Friis-Møller, Alice; Boisen, Nadia; Jønsson, Rie; Petersen, Randi F.; Petersen, Andreas M.; Krogfelt, Karen A. (Frontiers in Cellular and Infection Microbiology, 2017)
Enteroaggregative Escherichia coli (EAEC) is frequently found in diarrheal stools worldwide. It has been associated with persistent diarrhea, weight loss, and failure to thrive in children living in developing countries. A number of important EAEC virulence genes are identified; however, their roles in acute and persistent diarrhea have not been previously investigated. The aim of this study was to identify specific EAEC virulence genes associated with duration and type of diarrhea in Danish children. We aimed to improve the current diagnostics of EAEC and enable targeting of strains with an expected severe disease course. Questionnaires answered by parents provided information regarding duration of diarrhea and presence of blood or mucus. A total of 295 EAEC strains were collected from children with acute (≤7 days) and persistent diarrhea (≥14 days) and were compared by using multiplex PCR targeting the genes sat, sepA, pic, sigA, pet, astA, aatA, aggR, aaiC, aap, agg3/4C, ORF3, aafA, aggA, agg3A, agg4A, and agg5A. Furthermore, the distribution of EAEC genes in strains collected from cases of bloody, mucoid, and watery diarrhea was investigated. The classification and regression tree analysis (CART) was applied to investigate the relationship between EAEC virulence genes and diarrheal duration and type. Persistent diarrhea was associated with strains lacking the pic gene (p = 0.002) and with the combination of the genes pic, sat, and absence of the aggA gene (p = 0.05). Prolonged diarrhea was associated with the combination of the genes aatA and astA (p = 0.03). Non-mucoid diarrhea was associated with strains lacking the aatA gene (p = 0.004). Acute diarrhea was associated with the genes aggR, aap, and aggA by individual odds ratios. Resistance toward gentamicin and ciprofloxacin was observed in 7.5 and 3% of strains, respectively. Multi-drug resistance was observed in 38% of strains. Genetic host factors have been associated with an increased risk of EAEC-associated disease. Therefore, we investigated a panel of risk factors in two groups of children—EAEC-positive and EAEC-negative—to identify additional factors predisposing to disease. The duration of breastfeeding was positively correlated with the likelihood of belonging to the EAEC-negative group of children.